Synthesis, Optical and Photoluminescence Properties of Cu-Doped Zno Nano-Fibers Thin Films: Nonlinear Optics - Ganesh, V.; Salem, G. F.; Yahia, I. S.; Yakuphanoğlu, Fahrettin (Springer, 2018)
Different concentrations of copper-doped zinc oxide thin films were coated on a glass substrate by sol-gel/spin-coating technique. The structural properties of pure and Cu-doped ZnO films were characterized by different techniques, i.e., atomic force microscopy (AFM), photoluminescence and UV-Vis-NIR spectroscopy. The AFM study revealed that pure and doped ZnO films are formed as nano-fibers with a granular structure. The photoluminescence spectra of these films showed a strong ultraviolet emission peak centered at 392 nm and a strong blue emission peak cantered at 450 nm. The optical band gap of the pure and copper-doped ZnO thin films calculated from optical transmission spectra (3.29-3.23 eV) were found to be increasing with increasing copper doping concentration. The refractive index dispersion curve of pure and Cu-doped ZnO film obeyed the single-oscillator model. The optical dispersion parameters such as E-o, E-d , and n(infinity)(2) were calculated. Further, the nonlinear refractive index and nonlinear optical susceptibility were also calculated and interpreted.
Keywords: Cu-doped ZnO; nano-fibers; sol-gel/spin-coating method; AFM; photo-luminescence; optical dispersion parameters; nonlinear optics